Double-rail encoded self-timed adder with matched delays - Amin, A. (2003)
An efficient self-timed adder with low area overhead and efficient acknowledge slack time is proposed. The adder uses double-rail encoding of the carry signals as well as process-tracking matching delays to guarantee proper generation of the completion signal.